2003
DOI: 10.1007/s00259-002-1096-7
|View full text |Cite
|
Sign up to set email alerts
|

[18F]FMISO and [18F]FDG PET imaging in soft tissue sarcomas: correlation of hypoxia, metabolism and VEGF expression

Abstract: Hypoxia imparts resistance to radiotherapy and chemotherapy and also promotes a variety of changes in tumor biology through inducible promoters. The purpose of this study was to evaluate the use of positron emission tomography (PET) imaging with fluorine-18 fluoromisonidazole (FMISO) in soft tissue sarcomas (STS) as a measure of hypoxia and to compare the results with those obtained using [(18)F]fluorodeoxyglucose (FDG) and other known biologic correlates. FDG evaluates energy metabolism in tumors while FMISO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(149 citation statements)
references
References 45 publications
3
144
1
1
Order By: Relevance
“…To compare these data with the immunohistochemical measurements, the staining-positive fractions of PIMO and CA IX were multiplied with the corresponding tumour volumes to obtain the respective hypoxic volumes. The decision to use hypoxic volumes rather than hypoxic fractions is also supported by Rajendran et al (2003), who discussed the fact that the use of hypoxic fractions is a variable with considerable uncertainty.…”
Section: Discussionmentioning
confidence: 98%
“…To compare these data with the immunohistochemical measurements, the staining-positive fractions of PIMO and CA IX were multiplied with the corresponding tumour volumes to obtain the respective hypoxic volumes. The decision to use hypoxic volumes rather than hypoxic fractions is also supported by Rajendran et al (2003), who discussed the fact that the use of hypoxic fractions is a variable with considerable uncertainty.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we adopted the criterion suggested by Rajendran et al (19) of a T/B ratio of ≄1.2 to delineate tumor hypoxia. Our results included an analysis of the voxel-by-voxel FMISO voxel uptake within the entire tumor volume from repeat PET studies, with and without applying a T/B threshold criterion.…”
Section: Discussionmentioning
confidence: 99%
“…Rajendran et al (18) showed the feasibility of this approach using 18 F-FMISO PET to detect tissue hypoxia (corresponding to pO 2 values of ≀3 mm Hg) in imaging studies and showed that 18 F-FMISO uptake was directly related to tissue hypoxia (19). Different tumor/blood and tumor/muscle threshold ratios have been proposed as quantitative criteria for delineating hypoxic tumor volumes (19)(20)(21)(22)(23). To our knowledge, no standard PET criterion for defining hypoxia has yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Tumors, however, consistently rely on glycolysis even in the presence of abundant oxygen (Beckner et al, 2005;Griguer et al, 2005;Kelloff et al, 2005;Rajendran et al, 2003). Since the anaerobic metabolism of glucose to lactic acid is substantially less efficient than oxidation to CO 2 and H 2 O, tumor cells must increase glucose flux in order to maintain sufficient ATP production.…”
Section: The Warburg Effectmentioning
confidence: 99%